Association Between Environmental Health, Ecosystem Vitality, and Early Childhood Caries - Folayan, Morenike O.; El Tantawi, Maha; Schroth, Robert J.; Kemoli, Arthur M.; Gaffar, Balgis; Amalia, Rosa; Feldens, Carlos A.; , ECCAG (Frontiers in Pediatrics, 2020)
Background: Environmental issues lead to serious health problems in young growing children. This study aims to determine the association between a country's level of environmental health, ecosystem vitality, and prevalence of early childhood caries (ECC). Methods: This was an ecological study. The data for the explanatory variables—country-level environmental performance index (EPI), environmental health, and ecosystem vitality—were obtained from the Yale Center for Environmental Law and Policy. The outcome variables were country-level prevalence of ECC in 0- to 2-year-old and 3- to 5-year-old children. The country EPI, environmental health, and ecosystem vitality were matched with country ECC prevalence for 0- to 2-year-olds and 3- to 5-year-olds for the period of 2007 to 2017. Differences in the variables by country income level were determined using ANOVA. Multivariate ANOVA was used to determine the association between ECC prevalence in 0- to 2-year-olds and 3- to 5-year-olds, and EPI, environmental health, and ecosystem vitality, adjusting for each country's per-capita gross national income. Results: Thirty-seven countries had complete data on ECC in 0- to 2-year-old and 3- to 5-year-old children, EPI, environmental health, and ecosystem vitality scores. There were significant differences in ECC prevalence of 0- to 2-year-olds and 3- to 5-year-olds between countries with different income levels. Also, there were significant differences in EPI (P < 0.0001), environmental health score (P < 0.0001), and ecosystem vitality (P = 0.01) score by country income levels. High-income countries had significantly higher EPI scores than did low-income countries (P = 0.001), lower-middle-income countries (P < 0.0001), and upper-middle-income countries (P < 0.0001). There was an inverse non-significant relationship between ECC prevalence and EPI in 0- to 2-year-olds (B = −0.06; P = 0.84) and 3- to 5-year-olds (B = −0.30; P = 0.50), and ecosystem vitality in 0- to 2-year-olds (B = −0.55, P = 0.08) and 3- to 5-year-olds (B = −0.96; P = 0.02). Environmental health was directly and non-significantly associated with ECC in 0- to 2-year-olds (B = 0.20; P = 0.23) and 3- to 5-year-olds (B = 0.22; P = 0.32). Conclusions: There was a complex relationship between various indicators of environmental performance and ECC prevalence. The association with EPI and ecosystem vitality was inverse whereas the association with environmental health was direct. Only the inverse association with ecosystem vitality in 3–5 year old children was significant. There may be higher risk of ECC with greater economic development, industrialization, and urbanization, while better ecosystem vitality may offer protection against ECC through the rational use of resources, healthy life choices, and preventive health practices.